2019
DOI: 10.1371/journal.pone.0214703
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genes and alleles involved in the control of flowering time in grapevine

Abstract: Grapevine ( Vitis vinifera ) is one of the most important perennial crop plants in worldwide. Understanding of developmental processes like flowering, which impact quality and quantity of yield in this species is therefore of high interest. This gets even more important when considering some of the expected consequences of climate change. Earlier bud burst and flowering, for example, may result in yield loss due to spring frost. Berry ripening under higher temperatures will impact wine q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 86 publications
1
14
0
Order By: Relevance
“…A large number of genes following the flowering time control family (including FCA , FPA , and FY identified in our work) have been identified in grapevine ( Kamal et al, 2019 ), as the main genes involved in the high complex flower development and long duration of bud initiation, and in Arabidopsis thaliana , in which promote the transition of the vegetative meristem to reproductive development.…”
Section: Discussionmentioning
confidence: 78%
“…A large number of genes following the flowering time control family (including FCA , FPA , and FY identified in our work) have been identified in grapevine ( Kamal et al, 2019 ), as the main genes involved in the high complex flower development and long duration of bud initiation, and in Arabidopsis thaliana , in which promote the transition of the vegetative meristem to reproductive development.…”
Section: Discussionmentioning
confidence: 78%
“…Many of these QTLs had a minor effect on the trait (7-14%) and showed little overlap with the other study. More recently, a study looked at genes and alleles associated with early owering time and found positive candidates near QTL regions on chr 1, 4, 14, 17, and 18, suggesting that many, if not all of these regions may be useful for selecting early owering time in grape depending on the genetic background(Kamal et al, 2019). We identi ed a single QTL on chromosome 18 explaining ~ 11% of the variability observed.…”
mentioning
confidence: 76%
“…Unfortunately, many of these traits are associated with multiple small effect QTL dispersed across the grape genome. Flowering time and veraison time were associated with QTL of varying effects on chromosomes 1, 4, 8, 9, 10, 11, 13, 14, 17, 18, and 19, depending on the parentage of the cross (Fechter et al 2014; Kamal et al 2019; Underhill et al 2020). Two of those QTL on chromosomes 1 and 17 were consistently identi ed in two populations evaluated across two years (Fechter et al 2014).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Specifically, QTL associated with grapevine phenology, i.e. flowering time and the degree-day interval from budbreak to flowering, were previously detected on chromosomes 14 and 17, and 7 and 14, respectively [ 44 , 45 ]. Therefore, the effect of phenological variation on malate levels and their associated QTL identified here, were evaluated by using TSS as a proxy for fruit ripening and by performing genotype-specific sampling in the fifth year of the study (2019).…”
Section: Discussionmentioning
confidence: 99%